Low-Dose Caffeine Supplementation Is a Valuable Strategy for Increasing Time to Exhaustion, Explosive Power, and Reducing Muscle Soreness in Professional Male Kickboxers - Maziar Saremi; Fatemeh Shahriari; Mohammad Hemmatinafar; Rasoul Rezaei; Alireza Niknam; Michael Nordvall; Alexei Wong; Reza Bagheri (Current Developments in Nutrition)
Background: Caffeine is a well-established ergogenic aid that enhances physical performance and recovery. However, its dose-dependent effects on key performance metrics in combat sports like kickboxing remain insufficiently explored. Objective: This study aimed to evaluate the effects of varied doses of acute caffeine supplementation on performance indices and perceived muscle pain in kickboxing athletes. Methods: Twelve kickboxing athletes participated in 3 exercise sessions with either caffeine supplementation (3 mg/kg [C3], 6 mg/kg [C6]) or placebo (PLA). A 1-wk washout period occurred between exercise trials. Caffeine was supplemented 60 min before each exercise session. In each session, participants first performed a vertical jump and the Wingate anaerobic tests. After a 45-min rest, they completed the Bruce maximal aerobic treadmill test. Measured performance variables included vertical jump height, Wingate test outcomes (relative power [peak, mean power, and lowest], and fatigue index), maximal oxygen consumption (VO₂max), oxygen consumption at the ventilatory threshold (VT2), time-to-exhaustion, rating of perceived exertion (RPE), and muscle soreness assessed immediately, at 2 h, and 12 h postexercise. Results: C3 and C6 significantly increased time-to-exhaustion following treadmill testing (P < 0.05) but had no effect on the Wingate fatigue index (P > 0.05). Compared with PLA, C3 and C6 significantly increased vertical jump (P < 0.05). C3 significantly increased relative peak power (P < 0.05), whereas C6 and PLA did not during the Wingate test (P > 0.05). Muscle soreness after 2 h showed a significant decrease after C6 compared with C3 and PLA (P < 0.05). In contrast, no significant effect was observed for VO2max, %VO2max at VT2, and RPE (P > 0.05) for all treatments. Conclusions: Acute supplementation of 3 to 6 mg/kg doses of caffeine-induced relative improvements in anaerobic and lower-body muscular power, muscle soreness, and time-to-exhaustion in male kickboxing athletes.